Analisis Sikap Mahasiswa terhadap Penggunaan Microsoft Teams sebagai Media Tutorial Webinar (Tuweb) - Zakirman Zakirman; Chichi Rahayu (Universitas Indraprasta PGRI Jakarta, 2022)
Due to the Covid-19 pandemic, a new policy was implemented in Indonesian Education for all educational units. Webinar tutorials can represent learning during the Covid-19 pandemic. The Universitas Terbuka (UT) as the only public universities (PTN) in Indonesia based on open and distance higher education (PTTJJ) also implements webinars tutorials to support online lectures. This type of research is descriptive qualitative which aims to describe the analysis of student attitudes towards the use of Microsoft Teams as a medium for webinar tutorials (Tuweb). The population of this study was the students of UPBJJ-UT Padang study group (pokjar) Harau even semester 2020/2021 a total of 22 people in science learning courses in elementary school. The data instrument was observation sheets and interviews. Researchers used as a reference six indicators in analyzing student activities during the webinar tutorial using Ms. Teams. Based on the results of this study, the overall average percentage for the six indicators of active student attitude activity was 74.48% in the good category, while the passive was 27.93% in the very poor category. This shows that the attitude of students is more fun and motivated to use Microsoft Teams during webinar tutorials.